Analisis Pengaruh Pertumbuhan Ekonomi, Jumlah Angkatan Kerja dan Upah Minimum Regional Terhadap Pengangguran Terdidik di Jawa Timur - R. Achmad Ryan Z; Nanik Istiyani; Anifatul Hanim (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
This research aimed to determine how much the influence of economic growth, the number of labor force and regional minumum wages on educated unemployment in East Java. The data used in this research is secondary data such as time series and cross section. The analytical method used in this research is panel data regression analysis. The results showed that variable of the economic growth was positifly and not significantly affect to the educated unemployment in East Java, whereas the number of labor force and regional minimum wages was positivly and significantly affect to the educated unemployment in East Java. Keywords: The Economic Growth, the Number of Labor Force and Regional Minimum Wages.